Multinationality, portfolio diversification, and asymmetric MNE performance: The moderating role of real options awareness - Ioulianou, Sophocles P.; Leiblein, Michael J.; Trigeorgis, Lenos (Journal of International Business Studies, 2021)
The field of international business is fundamentally concerned with the implications of managerial actions that affect multinational risk and performance outcomes. While portfolio diversification and real options theory are often used to describe the outcomes of multinational investment, existing work often confuses the actions and predictions proposed by these theories. This is concerning, as the two theories emphasize different causal mechanisms, managerial actions, and conceptions of risk and performance. Whereas portfolio theory argues that passive management affects symmetric outcomes, such as variance in returns by attaining a well-diversified portfolio, real options theory posits that managers actively shift subsidiary resources to affect asymmetric outcomes, such as upside potential or downside risk by monitoring and responding to environmental changes affecting the portfolio. This paper disentangles these two theories by focusing on unique predictions from real options theory – that geographic dispersion of MNE activities is associated with asymmetric outcomes, that this association is contingent on management being aware of real options logic, and that these effects are moderated by the degree of market uncertainty. Our findings confirm these predictions and suggest differences in the types of managerial strategies and actions required to effectively implement these distinct theories of the MNE.